A multi-omics insight on the interplay between iron deficiency and N forms in tomato - Lodovici, Arianna; Buoso, Sara; Miras-Moreno, Begoña; Lucini, Luigi; Tomasi, Nicola; García-Pérez, Pascual; Pinton, Roberto; Zanin, Laura (Frontiers in Plant Science, 2024)
Nitrogen (N) and iron (Fe) are involved in several biochemical processes in living organisms, and their limited bioavailability is a strong constraint for plant growth and yield. This work investigated the interplay between Fe and N nutritional pathways in tomato plants kept under N and Fe deficiency and then resupplied with Fe and N (as nitrate, ammonium, or urea) through a physiological, metabolomics and gene expression study.After 24 hours of Fe resupply, the Fe concentration in Fe-deficient roots was dependent on the applied N form (following the pattern: nitrate > urea > ammonium > Fe-deficient control), and whereas in leaves of urea treated plants the Fe concentration was lower in comparison to the other N forms. Untargeted metabolomics pointed out distinctive modulations of plant metabolism in a treatment-dependent manner. Overall, N-containing metabolites were affected by the treatments in both leaves and roots, while N form significantly shaped the phytohormone profile. Moreover, the simultaneous application of Fe with N to Fe-deficient plants elicited secondary metabolites' accumulation, such as phenylpropanoids, depending on the applied N form (mainly by urea, followed by nitrate and ammonium).After 4 hours of treatment, ammonium-and urea-treated roots showed a reduction of enzymatic activity of Fe(III)-chelate reductase (FCR), compared to nitrate or N-depleted plants (maintained in Fe deficiency, where FCR was maintained at high levels). The response of nitrate-treated plants leads to the improvement of Fe concentration in tomato roots and the increase of Fe(II) transporter (IRT1) gene expression in tomato roots.In conclusion, our results strengthen and improve the understanding about the interaction between N and Fe nutritional pathways, thinning the current knowledge gap.